الوقاية من الفساد في الصفقات العمومية مساهمة من أجل تجاوز بعض العقبات العالقة - شرابي, عبد العزيز; خلاطو, فريد (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES)
يدخل هذا البحث في إطار تفكيك البنى المؤسساتية للتكسب الريعي من أجل تنظيم سلوك بعض الأطراف الناشطة    في السوق بالشكل الذي يضمن الوقاية   من الفساد. و يهدف إلى إعطاء عناصر للتفكير، و تسليط الضوء على بعض الجوانب النظمية للفساد في ميدان الصفقات العمومية بغية جعلها تبرم و تنفذ و تراقب في إطار الفعالية الشفافية       و العدل و المنافسة  و مراعاة الأخلاق. الكلمات الرئيسية : الصفقات العمومية ،الفساد النظمي ،الحوكمة ،الوقاية      من الفساد،الثقافة و الأخلاق.   This research includes the dismantling of institutional structures of rent-seeking in order to regulate the behavior of active parts in the market in the way that insure corruption’s prevention. In addition to that, the purpose is to give elements for thinking and highlight some aspects of systemic corruption in the public procurement’s field, for the aim of making public transaction concluded, executed, and controlled with transparency, justice, competition and ethics. keywords: Public procurement, systemic corruption, governance, prevention of corruption, culture and ethics.